Single centre experience with Nivolumab as monotherapy in chirrotic patients with advanced HCC. (March 2023) - Gaia, S.; Frigo, F.; De Giorgi, A.; Caviglia, P.; Rolle, E.; Pochettino, P.; Scaldaferri, M.; Cattel, F.; Risso, A.; Saracco, GM; Carucci, P
Abstract : Nivolumab monotherapy has proven to be effective sometimes for advanced HCC and could be a valuable treatment option for patients outside current treatment indications and reimbursement criteria for the standard of care. Aim: To evaluate the effectiveness of nivolumab off label monotherapy in patients with advanced HCC who are not eligible for other treatments. Methods: This is a retrospective study including 22 patients with advanced HCC from A.O.U. Città della Salute e della Scienza di Torino. Patients had prior sistemic therapy or were intolerant or ineligible for other treatments. They received nivolumab 3 mg/kg in monotherapy, every two weeks intravenously until disease progression, severe adverse events or death. Overall Survival (OS), Radiological Response (RR) (defined as stable disease, complete or partial response), Biological Response (BR) (defined as a decrease of ≥ 25% in AFP blood level at 3 months) are reported. A safety profile is reported. Results: OS was 7.8 months (95% CI 4, 7-14, 2, range: 1.1-32.6 months). The RR rate at 3 months was 36% (8/22 pts) and BR was 46% (6/13 pts). OS was significantly associated to the RR at 3 months (p 0.0001) and to BR (p 0.0001). Median OS in patients with Radiological response at 3 months was 27.7 months (CI 95% 4.7-27.7) vs 6.4 months in patients with disease progression (95% CI 3.2-9.1, p 0.0001). At baseline, performance status (ECOG), presence of metastatic lymph-nodes, bilobar hepatic involvement vs monolobar were related to a better OS (p 0.003). Grade 2 or 3 adverse events occurred in 36% of patients. No patients ceased nivolumab due to directly related adverse events. Conclusion: Nivolumab monotherapy could be a good treatment choice in selected patients with HCC who are ineligible for the standard of care. Radiological and biological response at 3 months predict long survivors. Overall Nivolumab was well tollerated.